Analysis of Household Financial Management of Millennial Muslim Mothers: A Study of Household Accounting Implementation in Tanete Riattang District, Bone Regency - A.Siti Nur Afida; Jumarni, Jumarni; Hasni, Hasni (Business Finance Analyst Co., 2024)
This study aims to analyze household financial management by millennial Muslim mothers in Tanete Riattang District, Bone Regency, by highlighting the implementation of household accounting. Financial management is a challenge in itself amidst modern lifestyles, economic pressures, and increasing expectations for quality of life. In this context, household accounting plays a role as an important tool for managing family finances in a structured, effective, and sharia-compliant manner. This study uses a qualitative approach. Data were obtained through in-depth interviews, observations, and documentation with millennial Muslim mothers as research subjects. The results of the study indicate that the implementation of household accounting, such as recording cash flow and preparing a budget, helps improve family financial stability. However, challenges such as lack of financial literacy, time constraints, and the pressure of a consumptive lifestyle are still significant obstacles. This study provides practical and theoretical contributions in understanding sharia-based household financial management, as well as being a reference for educational institutions, government, and the community in developing family financial empowerment programs. Keywords: Financial Management, Millennial Muslim Mothers, Household Accounting.